A Robust Test for Weak Instruments in Stata. (April 2015) - Pflueger, Carolin E.; Wang, Su
We introduce a routine, weakivtest, that implements the test for weak instruments by Montiel Olea and Pflueger (2013, Journal of Business and Economic Statistics 31: 358–369).weakivtest allows for errors that are not conditionally homoskedastic and serially uncorrelated. It extends the Stock and Yogo (2005, Testing for weak instruments in linear IV regression. In Identification and Inference for Econometric Models: Essays in Honor of Thomas Rothenberg, ed. D. W. K. Andrews and J. J. Stock, 80–108. [Cambridge University Press]) weak-instrument tests available inivreg2 and in theivregress postestimation commandestat firststage. weakivtest tests the null hypothesis that instruments are weak or that the estimator's Nagar (1959, Econometrica 27: 575–595) bias is large relative to a benchmark for both two-stage least-squares estimation and limited-information maximum likelihood with one endogenous regressor. The routine can accommodate Eicker–Huber–White heteroskedasticity robust estimates, Newey and West (1987, Econometrica 55: 703–708) heteroskedasticity- and autocorrelation-consistent estimates, and clustered variance estimates.